Improving Dance Learning Outcomes Using Demonstration Methods at SMK Negeri 7 Padang - Sri Okta Dinata, Vanesa; Astuti, Fuji (Universitas Negeri Padang, 2023)
The purpose of this study was to improve dance learning outcomes by using demonstration methods at SMK Negeri 7 Padang. A type of applied research is classroom action research. Tahao in this study, namely the stages of planning, implementation, observation and reflection. Observation boards, final tests and skill (practice) tests are used as aids in research. Data collection techniques through observation, tests and documentation. The results showed that the demonstration method with teachers as a direct example can improve student learning activities and dance learning outcomes. In Cycle 1 there is an increase in student learning, but not all students are able to carry out learning activities correctly. For Cycle II the teacher makes improvements that occur in Cycle I, the teacher guides students in practice with groups, visits students and does exercises. The average student learning outcome in Cycle I is 50% with poor criteria. After improvements were made in Cycle II, the average student achievement increased to 83 percent with good criteria. The use of demonstration methods in dance learning in class X Dance 2 also affects the average learning outcomes of students. The average learning outcomes of students before using the demonstration method were 50, the increase after using the demonstration method in Cycle I averaged 61.1. Because it did not reach the KKM of 70, then the race again in Cycle II and reached 85.6. So that through the demonstration method in the cultural arts class, the average score of class X Dance 2 students can be achieved above KKM.